Ultrasound radiomics models improve preoperative diagnosis and reduce unnecessary biopsies in indeterminate thyroid nodules - Chen, Lu; Wang, Yan; Jing, Haoyu; Bao, Rui; Sun, Bin; Zhang, Mingbo; Luo, Yukun (Frontiers in Endocrinology, 2025)
PurposeCytologically indeterminate thyroid nodules constitute 20–30% of fine-needle aspiration samples obtained from suspicious thyroid nodules. Over half of patients with indeterminate thyroid nodules undergo diagnostic surgery; however, 60–80% of excised nodules are benign. While some radiomics studies have built models to enhance the diagnostic efficacy of thyroid nodules, few have focused on indeterminate thyroid nodules with confirmed pathological results. We aimed to develop and evaluate ultrasound radiomics models to improve the diagnosis of indeterminate thyroid nodules and reduce unnecessary surgeries.MethodsWe retrospectively analyzed ultrasound images of 197 indeterminate thyroid nodules with definitive pathological results. Regions of interest were manually delineated using 3-Dimensional Slicer software, and radiomics features were extracted using Pyradiomics software. Ultrasound radiomics feature selection and dimensionality reduction were performed using univariate analysis and the least absolute shrinkage and selection operator method. Independent training (n=136) and validation (n=61) cohorts were used to develop three radiomics models. Model performance was evaluated using receiver operating characteristic analysis and compared to two existing assisted diagnostic tools and two junior radiologists.ResultsThe Radunion model achieved the highest performance, with 90.5% sensitivity, 56.8% specificity, 75.0% positive predictive value, 80.7% negative predictive value, and 76.6% accuracy. The Radsize model minimized biopsies by 21.1%, reducing the rate from 48.9% to 13.8%. These models outperformed the ITS 100 system, Thynet deep learning-based tools (p < 0.05), and junior radiologists.ConclusionUltrasound radiomics models are promising, convenient, and accurate adjunct tools for predicting malignancy, improving junior radiologists’ diagnostic performance, reducing unnecessary biopsies, and enhancing diagnostic precision in clinical practice.